A sociophonetic account of onset /s/ weakening in Salvadoran Spanish: Instrumental and segmental analyses. (22nd October 2018) - Brogan, Franny D.; Bolyanatz, Mariška A.
Abstract: In this study, we identify the linguistic and social predictors that condition onset /s/ weakening in speech data from sociolinguistic interviews with 72 Salvadoran Spanish speakers. In addition, we compare and contrast the explanatory power of instrumental and traditional segmental approaches. We find that the instrumental approach, which identifies flanking segments, stress, and region of origin of the speaker as conditioners of onset /s/ shortening and lowering of center of gravity, does not account for observed social variation in the data. Contrastingly, an ordinal logistic regression based on a combination of instrumental measures and perceived phonetic categories identifies flanking segment, region of origin, sex, and age of the speaker as predictors of onset /s/ weakening. We conclude that an exclusively instrumental analysis examining variation of onset /s/ thus obscures the potential social meaning of onset /s/ weakening in El Salvador.